Principal Self-Efficacy, School Climate, and Teacher Retention: A Multi-Level Analysis - Dahlkamp, Sundie; Peters, Michelle; Schumacher, Gary (Alberta Journal of Educational Research, 2018)
This article presents the findings of a correlational study that examines the relationship among the variables of principal self-efficacy, school climate, and teacher retention. A purposeful sample of 11 principals from a southeastern Texas school district were given the Principal Sense of Efficacy Scale to determine each individual’s level of self-efficacy. Simultaneously, a sample of 233 current and former teachers completed the Organizational Climate Index to measure the school climate of each participating school. The results of the multi-level analysis indicate that overall a relationship does not exist between either principal self-efficacy and teacher retention or principal self-efficacy and school climate. However, findings do suggest a relationship between teacher retention and school climate. More specifically, teachers are more likely to remain employed at campuses that are less influenced by vocal parent and citizen groups. Cet article présente les résultats d’une étude corrélationnelle portant sur le rapport entre trois variables : l’efficacité personnelle des directeurs d’école, le climat scolaire et la rétention des enseignants. Suivant un échantillonnage dirigé, 11 directeurs d’un district scolaire dans le sud-est du Texas ont répondu à un questionnaire portant sur leur sentiment d’efficacité personnelle. Pendant la même période, 233 enseignants (anciens et actuels) ont complété un questionnaire sur le climat organisationnel de sorte à mesurer le climat scolaire dans chaque école participante. Les résultats d’une analyse à plusieurs niveaux indiquent que, globalement, il n’y a pas de lien entre l’efficacité personnelle des directeurs et la rétention des enseignants, ni entre l’efficacité personnelle des directeurs et le climat scolaire. Toutefois, les résultats suggèrent un rapport entre la rétention des enseignants et le climat scolaire. Plus précisément, les enseignants sont plus portés à maintenir leur poste dans des écoles qui sont moins influencées par des groupes protestataires de parents et de citoyens.